2011
DOI: 10.3844/ajassp.2011.1086.1092
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Elements to Produce Sesame Yoghurt from Sesame Milk

Abstract: Problem statement:In previous work sesame milk was developed. The developed milk had slightly acceptable flavor and limited shelf life. Fermentation of sesame milk is one way to overcome these problems. Approach: Sesame yoghurt experiments were carried out using pasteurized sesame milk (75°C for 5 min) with 14% initial sesame seed concentration and 2.7% glucose with different dairy products: lactose, Cheese Dried Whey (CDW), Non Fat Dried Milk (NFDM) and skim milk. The formulas were fermented using commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Soy-based drinks are the dominant plant-based milk alternatives in the Western world (Mäkinen et al 2016). In addition, drinks based on almond (Ginsberg and Ostrowski 2007), coconut (Seow and Gwee 1997), sunflower seed (Fujisawa et al 1986), chickpea (Rao et al 1988), lupine (Ivanović et al 1983), hemp (Vahanvaty 2009), sesame (Afaneh et al 2011), quinoa (Pineli et al 2015), pea (Li et al 2004), and rice (Mitchell et al 1990) are available and contribute to the diversity of the plant-based milk alternative market. Depending on the individual raw materials, the corresponding drinks differ significantly in composition and flavour.…”
Section: Leading Plant-based Milk Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Soy-based drinks are the dominant plant-based milk alternatives in the Western world (Mäkinen et al 2016). In addition, drinks based on almond (Ginsberg and Ostrowski 2007), coconut (Seow and Gwee 1997), sunflower seed (Fujisawa et al 1986), chickpea (Rao et al 1988), lupine (Ivanović et al 1983), hemp (Vahanvaty 2009), sesame (Afaneh et al 2011), quinoa (Pineli et al 2015), pea (Li et al 2004), and rice (Mitchell et al 1990) are available and contribute to the diversity of the plant-based milk alternative market. Depending on the individual raw materials, the corresponding drinks differ significantly in composition and flavour.…”
Section: Leading Plant-based Milk Alternativesmentioning
confidence: 99%
“…3Macronutrient composition, functional components and limiting factors of common plants used for plant-based milk alternative production. The data are collected from previous work (Afaneh et al 2011; Bernat et al 2015; Callaway 2004; DebMandal and Mandal 2011; Duranti et al 2008; Erbaş et al 2005; Fernandez and Berry 1988; Hove 1974; Juliano and Hicks 1996; Lambo et al 2005; Lampart-Szczapa et al 2003; Lebiedzińska and Szefer 2006; Makinde and Akinoso 2013; Moneret-Vautrin et al 1999; Noimark and Cox 2008; Önning et al 1998; Paucar-Menacho et al 2010; Ranhotra et al 1993; Roy et al 2010; Seow and Gwee 1997; Sethi et al 2016; Škrbić and Filipčev 2008; Ulyatu et al 2015; Vahanvaty 2009; Vanga and Raghavan 2018; Vidal-Valverde et al 2003; Vilche et al 2003; Villamide and San Juan 1998; Wood and Grusak 2007). The micronutrient composition data are acquired from the National Nutrient Database for Standard Reference Release (NDB) (https://ndb.nal.usda.gov/ndb/).…”
Section: Leading Plant-based Milk Alternativesmentioning
confidence: 99%
“…Therefore, they are typically used for fermentation (21). For example, S. thermophilus and Lactobacillus have been used to produce sesame yogurt from sesame milk by Afaneh et al (22). Several studies have demonstrated antioxidant activity of sesame, however, there is no sufficient study on fermented sesame with lactic acid bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Like peanut and soybean, sesame seed can be processed to produce sesame milk (Shahidi 2006). However, Afaneh et al (2011) reported that flavor produced during fermentation by lactic acid can cover the unfavored flavor of sesame milk. This phenomenon may be associated with the glucosidase activity produced by lactic acid bacteria.…”
Section: Sensory Aspects Of Unfermented and Fermented Sesame Tahinimentioning
confidence: 99%